Pelatihan Pembuatan Media Pembelajaran Berbasis Canva di SDN No. 88 Jennae - Suriyati, Suriyati; Sausan, Rafiqa; Suriati, Suriati; Nur, Taufiq (LP2M Universitas Islam Ahmad Dahlan, 2025)
Learning media utilizes information technology so that learning situations that were initially learning with effort become learning with fun. Learning media is in the form of visual, audio and audio-visual. In this training, Canva design media is one of the choices as a learning media because it has various and interesting templates so it is in great demand by users, especially in the educational sphere. Creating interesting learning media can make it easier for students to comprehend and understand the material taught by the teacher and make students less bored in learning. If there is good communication or delivery process, students will easily understand the learning material presented by the teacher. In this training it can be concluded that there was an improvement before and after receiving the training. For teachers, media helps concretize concepts or ideas and helps motivate active learning participants. Canva is a graphic design application that helps teachers create various types of creative learning online. Using the Canva application can make it easier for elementary school teachers who are not skilled enough to utilize information technology in designing interactive learning. In this activity, the teachers of SDN No. 88 Jennae practiced creating Canva-based learning media. As a result, they were able to develop interesting learning media using the Canva application.